Peer-to-Peer (P2P) lending - Gonzalez, Laura (Henry Stewart Talks, 2014)
Intro, Outline, What is peer-to-peer lending?, Why the interest?, How does P2P lending work?, P2P vs. microfinance & crowdfunding, Previous research findings, Behavioral & Experimental motivation, When can a photo increase credit? The impact of lender and borrower profiles, Sample loan application, Some behavioral findings, International patterns, Summary & Conclusions